(untitled) (International Journal of Physiotherapy, 2021)
Background: Information about the burden of care and factors associated with it among caregivers of individuals with spinal cord injury is fundamental in planning programs to alleviate their burden. Methods: We conducted the study using a mixed-method design of the cross-sectional survey and qualitative study. Thirty-four participants (informal caregivers of individuals with spinal cord injury) for the study were purposively selected at the foremost tertiary hospital in Nigeria. The Zarit Burden Interview (ZBI) questionnaire was used to assess the level of burden of care. In addition, seven purposively selected informal caregivers also participated in the focus group discussion. Descriptive and inferential statistics were used to analyze the quantitative study, while the qualitative data were analyzed using thematic content analysis. Results: Findings of the cross-sectional study showed that 28 (82.4%) participants had a high level of burden of care. Significant associations were found between the burden of care and the level of income of participants (p=0.042), the burden of care, and the number of hours spent caring (p=0.005). The qualitative study revealed poor hospital administration and logistics, high cost of care, and negative attitude of health workers as what constitute the burden. Conclusion: The informal caregivers experience a high level of burden of care, associated with poor hospital administration, health workers attitude, and high cost of care.